Preclinical paired noninferiority study comparing in-house and commercially available 3D planning for corrective osteotomy of the distal radius - Charlotte Stor Swinkels; Katleen Libberecht; Emilia Gryska; Peter Axelsson; Per Fredrikson; Anders Björkman (Scientific Reports)
Abstract 3D surgical planning and patient-specific guide design are becoming an established approach in complex skeletal surgery. Traditionally, this is outsourced to commercial companies, but an alternative is to establish an in-house hospital team for the process. This study aimed to compare the accuracy of in-house design with a commercial company. Sixteen patients with extra-articular distal radius malunions requiring surgery were included. A hospital-based team and a surgeon working with an external company independently planned surgery and designed guides for each patient. Accuracy was evaluated by comparing simulated corrections with the planned corrections using 3D-printed bone models. The null hypothesis was that the in-house guides were inferior to the externally purchased ones. Noninferiority margins of 5° for volar tilt and 2 mm for ulnar variance were set. The mean volar tilt error difference between the two guides was 2.3°, and the mean ulnar variance error difference was 0.38 mm, both within the noninferiority limits. The dimensional accuracy of the printed guides before and after sterilization showed minimal variation (less than 0.3 mm). The results demonstrated that in-house surgical planning and guide design for distal radius corrective osteotomies can achieve comparable accuracy to external commercial companies.